The assessment of capable guardianship measures against bullying victimization in the school environment. (3rd March 2016) - Choi, Kyung-Shick; Cronin, Shea; Correia, Heather
Abstract: Policymakers, school officials and the law enforcement community have expanded legal tools and other strategies to address bullying in recent years. This has resulted in a larger and more challenging role for law enforcement officers working in school settings. The present study seeks to understand the ways in which local law enforcement officers interpret this new role and their efforts to prevent and respond to bullying. We draw upon Routine Activities Theory as a lens to view officer perceptions of promoting guardianship and reducing target suitability of young people most at-risk for bullying victimization. Data collected from qualitative interviews of law enforcement officers working with local schools, suggest that officers see a role for law enforcement in promoting guardianship around this health and safety concern, but recognize the limitations of using arrest authority. They emphasize promoting trust and building relationship in efforts to support potential and current bullying victims.